Utilização de Grafite Funcionalizado em Eletrodos de Pasta de Carbono para Detecção Simultânea de Ácido Ascórbico e Ácido Fólico em Amostra de Urina - Ferro, Érica de Castro; da Silva, Ana Caroline; de Arruda, Gilberto José (Orbital: The Electronic Journal of Chemistry, 2016)
This work describes the development of a sensor, using functionalized graphite in basic medium, to simultaneously detect ascorbic acid and folic acid. The graphite was functionalized in solution of    NaOH 4 mol L-1, before its use in the preparation of the carbon paste electrode. The electrochemical techniques of cyclic voltammetry and differential pulse voltammetry were used to characterize the redox process, which occurs in the working electrode’s surface. The electrochemical impedance spectroscopy was used to characterize the influence of the functionalization in the electrical properties of the electrode-solution interface. The obtained results showed that the functionalization increases the electrocatalytic activity of the graphite, verified by an increase of about 1.8x in the peak of oxidation current of both ascorbic and folic acid. The increase in the electrocatalytic activity of the functionalized graphite was due to a decrease in the resistance to charge transfer and an increase of the standard rate constant of reaction. The obtained results showed that carbon paste electrodes utilizing functionalized graphite can be used in simultaneous detection of ascorbic and folic acid. The sensor has been used successfully in the simultaneous detection of ascorbic acid and folic acid in human urine samples contaminated artificially. The results showed a recovery of 96-101% and a relative standard deviation less than 3%.DOI: http://dx.doi.org/10.17807/orbital.v8i3.820